Closing doors (1780-1813): the liquidation process at General Company of Pernambuco and Paraíba - Silva, Angélica de Vasconcelos (2016)
This dissertation investigated the dynamics, rationales and context of accounting practices in a pre-industrial setting. By focusing on the case of the General Company of Pernambuco and Paraíba (PPC), the examination could analyze a firm\'s entire lifecycle (from the birth until decline) to answer the following research question: How and why did the PPC\'s liquidation process stretch for so long? The PPC was a privately owned company whose monopoly privilege was granted by the Portuguese Crown in 1759 and suspended in 1780. Between the removal of the monopoly rights and 1813, the company \'got stuck\' in a liquidation despite using double-entry bookkeeping. The study preserves the historical integrity of the analysis using the mental frame of the PPC own time. Based on the premise that accounting cannot be isolated from the setting in which it plays a role, four context issues were chosen to answer the research question: (1) the relationship between the PPC and the Crown, (2) the organizational structure of the PPC, (3) the accounting system of the PPC, and (4) the ties between PPC\'s stakeholders. It shows how and why each factor evolved over time and contributed to the delay in the PPC\'s liquidation. The examination relies upon different archival sources, including the surviving corporate books prepared at two of PPC\'s business units. The applied research design was a case study. The Crown acted as the head of the PPC but did not exercise close control over directors. The continuity of the business was financially more attractive for the directors than the liquidation process. The corporate rules, mainly remuneration, created incentives for their behavior. The seats on the boards of the PPC were controlled by a small group of shareholders. The directors changed some accounts\' rationales for their benefit, and the accounting procedures were realized without zeal. The issued financial statements also created an unreal financial situation (overvaluation) which directors insisted on realizing during the liquidation. The PPC granted credit based on fragile criteria and without sufficient guarantees. In the liquidation, when the company needed to convert the receivables into cash, the lack of guarantees caused additional delay